PEMBERDAYAAN KELUARGA PASIEN DALAM PENCEGAHAN INFEKSI LUKA OPERASI DI RSU KEFAMENANU NTT - Simon Sani Kleden; Sabinus Bunga Ama Kedang; Christina Grasia Kellen; Yolanda Kuabib (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Wound healing process takes a long time, while time for hospitalization is short, so the surgical wound has a risk of infection. Family empowerment through education is one way for preventing surgical wound infections at home. The purpose of this study was to determine the effect of the patient's family empowerment through education on the ability of family members in the prevention of abdominal surgical wound infections at home. This was a pre-experimental research, using one group pre-post-test design on 30 family members of post-apedictomy, herniotomy, laparotomy, prostatectomy and varicocelectomy patients. Sampling method in this study was total sampling. Data were collected by measuring the level of knowledge, attitudes, and actions of family members using questionnaire and observation check-list before and after education regarding the prevention of abdominal surgical wound infection at home. Education was carried out prior to surgery, one day before the patient left the hospital, and one day after control patient returned to hospital. Patient care guidance was performed 4-7 times in the hospital and then the results were evaluated at home. Results showed that 28 people (93.30%) had good knowledge, 30 people (100%) had good attitude and actions after the education. The results of statistical tests using Wilcoxon Signed Rank Test p = 0.000, meaning that there were changes in the ability of family members in the prevention of abdominal surgical wound infections at home before and after education in the aspects of knowledge, attitudes, and actions. There were no patients experienced infection from surgical wound. These results illustrate that the empowerment of family members of patients in the prevention of surgical wound infection needs to be done by a nurse before surgery, during treatment, and before the patient leaving the hospital